Answer:
x = 7/6 + (i sqrt(95))/6 or x = 7/6 - (i sqrt(95))/6 thus NO, x^2 - (7 x)/3 = -4 would be correct.
Explanation:
Solve for x:
3 x^2 - 7 x + 12 = 0
Hint: | Write the quadratic equation in standard form.
Divide both sides by 3:
x^2 - (7 x)/3 + 4 = 0
Hint: | Solve the quadratic equation by completing the square.
Subtract 4 from both sides:
x^2 - (7 x)/3 = -4
Hint: | Take one half of the coefficient of x and square it, then add it to both sides.
Add 49/36 to both sides:
x^2 - (7 x)/3 + 49/36 = -95/36
Hint: | Factor the left hand side.
Write the left hand side as a square:
(x - 7/6)^2 = -95/36
Hint: | Eliminate the exponent on the left hand side.
Take the square root of both sides:
x - 7/6 = (i sqrt(95))/6 or x - 7/6 = -(i sqrt(95))/6
Hint: | Look at the first equation: Solve for x.
Add 7/6 to both sides:
x = 7/6 + (i sqrt(95))/6 or x - 7/6 = -(i sqrt(95))/6
Hint: | Look at the second equation: Solve for x.
Add 7/6 to both sides:
Answer: x = 7/6 + (i sqrt(95))/6 or x = 7/6 - (i sqrt(95))/6